Ciplukan (Physalis angulata L.) Juice as a Functional Food to Lower Blood Pressure in Hypertension Patients - Rizqi Annisa Permatasari; Lilik Retna Kartikasari; Anik Lestari (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Functional foods rich in bioactive compounds, such as flavonoids, have gained attention for their potential role in managing blood pressure. Physalis angulata L., commonly known as Ciplukan, is a tropical fruit with a high quercetin content, a flavonoid known for its antioxidant and vasodilatory properties. This study aims to evaluate the application of Ciplukan juice as a nutritional therapy on blood pressure in patients with hypertension. The study used a quasi-experiment pretest-posttest control group design. The quercetin content in the Ciplukan juice was analyzed using the High-Performance Liquid Chromatography (HPLC) method at the Technical Implementation Unit (UPT) Integrated Laboratory Universitas Diponegoro. The sample in this study was 47 individuals with hypertension from Gambirsari Health Center, Surakarta, Indonesia. Subjects were randomly divided into control and treatment groups. The control group was given amlodipine per day and nutrition education. The intervention group received amlodipine, nutrition education, and 250 ml of Ciplukan juice per day. The research was conducted for 30 days. Data analysis used the Mann-Whitney and Wilcoxon test. The test results showed a significant difference in systolic and diastolic blood pressure between the control and treatment groups with a p-value of 0.000. The reduction in systolic blood pressure in the treatment group was 20.5 mmHg greater than the control group. The decrease in diastolic blood pressure in the treatment group was 10.8 mmHg greater than in the control group. Consuming Ciplukan juice 250 ml per day for 30 days was suggested to reduce blood pressure in hypertension effectively.